Dual autoimmune diseases: Rheumatoid arthritis with systemic lupus erythematosus and Type 1 diabetes mellitus with multiple sclerosis. Issue 3 (20th April 2022) - Ahmad, Rizwan; Ahsan, Haseeb
Abstract: Autoantibodies and inflammation are the hallmarks of autoimmune diseases (ADs). Organ‐specific and nonorgan‐specific ADs are divided according to whether the autoimmune reaction is directed against a specific tissue (e.g., thyroid in Hashimoto's thyroiditis) or widely expressed antigens (e.g., cell nuclei in systemic lupus erythematosus [SLE]). SLE is distinguished by the presence of circulating autoantibodies and immune complex deposition, both of which can induce inflammatory damage to many organs. Rheumatoid arthritis (RA), sometimes called inflammatory arthritis, is a systemic AD that affects the joints and causes synovitis. Multiple sclerosis (MS) is a central nervous system inflammatory disease with various neurological and autoimmune symptoms. Links have been reported between RA and SLE as well as between Type 1 diabetes mellitus and MS. Identification of shared genes and biological processes could aid in the discovery of possible treatment targets in these dual ADs. This review article explores the molecular nature and familial inheritance of dual ADs. Abstract : Shared genetic loci and biomarkers in dual autoimmune disorders. Key points: Autoimmune diseases (ADs) can be classified into organ‐specific or nonorgan‐specific, that is, tissue specificity (e.g., thyroid in Hashimoto's thyroiditis) or against widely expressed antigens (e.g., nuclear antigens in systemic lupus erythematosus [SLE]). SLE is distinguished by the presence of circulating autoantibodies and immune complex deposition, both of which can induce inflammatory damage to the organs. Rheumatoid arthritis (RA), also known as inflammatory arthritis, is a systemic AD that affects the joints and causes synovitis. Multiple sclerosis (MS) is a central nervous system inflammatory disease with various neurological and autoimmune symptoms. Familial inheritance and genetic links have been reported between RA and SLE, and Type 1 diabetes mellitus and MS. Identification of shared major genes and biological pathways would be useful as a potential therapeutic targets and biomarkers in dual ADs.